PENGELOLAAN SUMBER DAYA ALAM BERDASAR PRINSIP FIQH AL-BI’AH - Fitrian Noor (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2018)
This article examined the concept of natural resource management based on the principles of fiqh al-bi’ah and reconstructs the main flow of thinking in the management model of exploitative natural resources. The state in many cases exploited certain sectors to increase state income and foreign exchange without regard to the principles of justice, economic democracy and the continued functioning of natural resources. So the urgency of managing natural resources based on fiqh al becomes important to offer. The method used the normative legal method. Based on the results of the research, the application of the fiqh principle of al bi’ah could give a doctrine of understanding how natural resources have been glorified, valued for their usefulness, and preserved as well as how our indigenous people allow natural resources and the principles of fiqh. al-bi’ah can be applied in the norm of the formation of legislation in the PSDA Bill.DOI: http://dx.doi.org/10.17977/um019v3i12018p047